HUBUNGAN POWER OTOT LENGAN DENGAN KEMAMPUAN MELAKUKAN SERVIS PANJANG PADA PERMAINAN BULUTANGKIS PADA SISWA PUTRA KELAS VIII SMPN 1 WANGI-WANGI - Muhammad Rusli; Hasanuddin Jumareng; Aliasis Maruka (Universitas Halu Oleo, 2021)
The aim of this research is to know the relationship between the limbs and the ability of lung-jump in the students of SMA Negeri 7 Kendari. The population in this study areall students of SMA Negeri 7 Kendari amounting to 520 consisting of 346 girls and 174 boys. The sample in this study was 35 people drawn with purposive random sampling technique based on the boy’s gender consideratio. While the instrumen use distheleg muscle power test by means of a standing broad jump test and a long jump ability test by doing a long jump. The result so btained from the hypothesis testing are muscular power of the limbs having a relationship with the ability of a distand jump where the sign if i cant value = 0.000<significant level α= 0.05. the correlation value obtained is 0.720 with a coefficient of determination 0.52 or 52% From the obtained results can be concluded that the reis a link between the muscular power of the limbs with the ability of long jump on high school students 7 Kendari.